The fae keeper - Edgmon, H. E. (Edgmon, H. E. Witch King duology, 2022)
"Two weeks after the door to Faery closed once more, Asalin is still in turmoil. Emyr and Wyatt are hunting Derek and Clarke themselves after having abolished the corrupt Guard, and are trying to convince the other kingdoms to follow their lead. But when they uncover the hidden truth about the witches' real place in fae society, it becomes clear the problems run much deeper than anyone knew. And this may be more than the two of them can fix"--